Multifunctional, Defect‐Engineered Metal–Organic Frameworks with Ruthenium Centers: Sorption and Catalytic Properties1. Issue 27 (18th May 2014) - Kozachuk, Olesia; Luz, Ignacio; Llabrés i Xamena, Francesc X.; Noei, Heshmat; Kauer, Max; Albada, H. Bauke; Bloch, Eric D.; Marler, Bernd; Wang, Yuemin; Muhler, Martin; Fischer, Roland A.
Abstract A mixed‐linker solid‐solution approach was employed to modify the metal sites and introduce structural defects into the mixed‐valence RuII/III structural analogue of the well‐known MOF family [M3II, II(btc)2] (M=Cu, Mo, Cr, Ni, Zn; btc=benzene‐1, 3, 5‐tricarboxylate), with partly missing carboxylate ligators at the Ru2 paddle‐wheels. Incorporation of pyridine‐3, 5‐dicarboxylate (pydc), which is the same size as btc but carries lower charge, as a second, defective linker has led to the mixed‐linker isoreticular derivatives of Ru‐MOF, which display characteristics unlike those of the defect‐free framework. Along with the creation of additional coordinatively unsaturated sites, the incorporation of pydc induces the partial reduction of ruthenium. Accordingly, the modified Ru sites are responsible for the activity of the "defective" variants in the dissociative chemisorption of CO2, the enhanced performance in CO sorption, the formation of hydride species, and the catalytic hydrogenation of olefins.